STUDI LITERATUR MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEAKTIFAN SISWA SEKOLAH DASAR - Aldo Febrian Pratama; Linda Zakiah; Juhana Sakmal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This literature study aims to analyze the impact of the Discovery Learning model on student activeness at the elementary school level. The Discovery Learning model emphasizes the active role of students in discovering learning concepts independently through exploration, observation, and analysis. This study reviews various sources such as journals, scientific articles, and previous research relevant to the implementation of Discovery Learning in elementary education. The findings indicate that the Discovery Learning model significantly enhances student engagement across cognitive, affective, and psychomotor aspects. Students become more enthusiastic, actively participate in discussions, and demonstrate increased curiosity and critical thinking skills. Therefore, Discovery Learning is considered an effective instructional approach in fostering participative and meaningful learning environments in primary education.